Human papillomavirus (HPV) DNA and mRNA primary cervical cancer screening: Evaluation and triaging options for HPV-positive women. (December 2019) - Sangrajrang, Suleeporn; Laowahutanont, Piyawat; Wongsena, Metee; Muwonge, Richard; Imsamran, Weerawut; Ploysawang, Pattama; Basu, Partha
Objective: Cervical cancer is the second most common cancer in Thai women; human papillomavirus (HPV) is the main cause. This study aimed to determine the clinical performance of HPV mRNA compared with HPV DNA testing. Methods: Cervical specimens were collected from women aged 35 to 60 who attended the routine organized screening programme. We compared accuracy parameters of standalone HPV mRNA and HPV DNA tests, and those of triaging with liquid-based cytology or HPV genotyping and liquid-based cytology for those positive only for the less oncogenic HPV types. Test accuracy parameters were estimated using latent class analysis using Bayesian models. Results: Of the 5046 women enrolled, 174 (3.4%) were HPV DNA positive and 141 (2.8%) HPV mRNA positive. Colposcopy compliance was 95.4% ( n  = 166) among HPV DNA-positive women and 94.3% ( n  = 133) among those HPV mRNA positive. The estimated sensitivity, specificity, and positive predictive value for detection of CIN2 or worse were 67.4%, 97.1%, 12.1% for HPV DNA testing, and 73.1%, 97.8%, 16.3% for HPV mRNA testing. These estimates for triaging of HPV DNA-positive women with liquid-based cytology were 64.4%, 98.8%, and 19.0%, respectively, and slightly better for liquid-based cytology triage of HPV mRNA-positive women, at 71.8%, 98.9%, and 22.1%. Conclusion: A triaging strategy based on HPV genotyping and liquid-based cytology for those positive only for the less oncogenic HPV types had test characteristics comparable with that of liquid-based cytology triage. The HPV mRNA detection-based strategies had non-significant advantages over the HPV DNA detection-based strategies.